Problems in Developing Seminar Course for Biology Education Students - Herawati Susilo (Bandar Lampung University (UBL), 2014)
Biology Education students should be prepared to write their ideas and present their ideas in a seminar. Two cycles of Classroom Action Research (CAR) was Done in developing Seminar Course for Biology Education Students in the second semesters of 2012/2013 and 2013/2014. For the first cycle of CAR the writer who was new in this course had a partner in conducting the course for two classes. At that time the seminar paper was targeted to prepare a research proposal. As a partner of an experienced lecturer, the writer did not face much problem because the writer just follow the partner. The writer also used to teach educational research course. At the beginning of the new year of 2013/2014 the writer present the sylabus content and the purposes of seminar course to be discussed in the Biology Department. The result of the lecturers’ discussion was that the seminar can be used to train the students to present ideas in (Biology) Education, it can be a research proposal or any ideas in Biology Education. For the second cycle the writer had one seminar class of 20 students and didn’t have partner in conducting the seminar course. The problems faced by the writer was in guiding students in finding the title of the seminar paper, in finding how to guide the students in using literature sources and in writing the seminar paper. The writer tried to answer the problem by conducting CAR with the action to give the students tasks to present the problems that were interested for the students, to do critical analysis of at least ten articles, to present the results of critical analysis of articles related to the background of the problem in front of the class and show the highlighted part of the articles that will be cited in the background of the problem, and to present the draft of the seminar paper. The results showed that students had tried their best in preparing the tasks but that the writer still had to give examples on how to give inputs to the presenter on how to improve the ideas and the presentation.